Pelatihan Pembuatan Permainan Edukatif Menggunakan Wordwall di Sekolah Dasar - Desy Rosmalinda; Risdalina Risdalina; Ahmad Syarif; Issaura Sherly Pamela; Erlida Amnie (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
The rapid advancement of technology underscores the importance of teachers’ ability to adapt and integrate digital tools into the learning process. To ensure the effective implementation of such technological adaptation in schools, continuous support and mentoring from educational partners are essential. This community service activity aimed to train teachers at SDN 205 Jambi in creating educational games using Wordwall, a web-based application that offers various engaging game templates. The training was conducted through several stages: material presentation, trial of educational games, hands-on practice in designing Wordwall-based games, and subsequent evaluation and reflection. As a result of this program, teachers successfully developed a range of educational games relevant to their classroom subjects. The level of teacher satisfaction with the training was evaluated using a quantitative approach through a Likert-scale questionnaire covering four dimensions: training content, facilitators, facilities and media, and overall satisfaction. The results revealed that teachers reported a very high level of satisfaction across all aspects of the training. The relevance of the training materials achieved an average score of 4,48 (very high category), while the facilitator quality received an average score of 4,49 (very high category). The facilities and instructional media were rated 4.46, also classified as very high. The final indicator, overall satisfaction, achieved an average score of 4,59, placing it firmly within the very high category. These findings highlight the importance of continuous, technology-oriented professional development programs to strengthen elementary school teachers’ digital competencies and support the integration of innovative learning tools in the classroom.